Coaches` experiences of performance support teams - Burns, A.; Collins, D.; Nolte, L. (International Journal of Sports Science & Coaching, 2024)
Supporting high-level performance is increasingly seen as a team game, reflected in the growth in support services. Coaches and management must work effectively with various practitioners to deliver the required support to athletes. To date, how coaches experience these support teams has yet to be explored. Accordingly, we utilized a qualitative research design with semistructured interviews to examine coach-consumers` perceptions of more or less effective practice. Eight high-level coaches were recruited, and data was analyzed using reflexive thematic analysis. Key themes generated included the make-up and conduct of high-performing teams, prioritizing coach-practitioner relationships, and professional development considerations for both coaches and practitioners. Data suggest that practitioners are seen as playing a crucial role in elite sports performance, and coaches generally have a positive view of the contributions of sports science teams. Notably, however, several challenges were identified, including communication issues, conflicts over the allocation of resources, recruitment of, and the need for sports scientists to understand the demands of sports and the coaching process. Findings have practical implications for support teams and coaches working in high-performance sports; specifically, in the recruitment and development of sports science and medicine practitioners and coaches.